2021
DOI: 10.2147/nss.s308968
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic Sleep and Attentional Deficits in Traumatized North Korean Refugees

Abstract: Introduction: Attentional deficits and sleep problems are common in refugees who have experienced trauma. In the present study, we used polysomnography (PSG) to investigate the relationship between attentional deficits and objective measures of sleep structure in traumatized North Korean refugees. Methods: We recruited 32 North Korean refugees (mean age = 33.78 ± 14.33 years) and 39 South Korean participants (mean age = 35.03 ± 11.08 years). Sustained attention and divided attention were assessed using the Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…26 The range of CPTSD prevalence was 11.3% 27 to 40.7%, 9 while another study reported a lifetime prevalence of 15.3%. 11 Twenty-four studies were conducted with participants living in the community, 9,11,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][46][47][48]61,62 8 studies at Hanawon (The Settlement Support Center for North Korean defectors), 26,27,[50][51][52][53][54][55] 6 studies at medical centers, 25,45,48,[56][57][58][59] and 2 studies were conducted using an online survey. 49,60 Out of 40 studies reviewed, only one study reported the longitudinal trajectories of the mental health of North Korean defectors.…”
Section: General Characteristics Of the Included Proms And Studiesmentioning
confidence: 99%
“…26 The range of CPTSD prevalence was 11.3% 27 to 40.7%, 9 while another study reported a lifetime prevalence of 15.3%. 11 Twenty-four studies were conducted with participants living in the community, 9,11,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][46][47][48]61,62 8 studies at Hanawon (The Settlement Support Center for North Korean defectors), 26,27,[50][51][52][53][54][55] 6 studies at medical centers, 25,45,48,[56][57][58][59] and 2 studies were conducted using an online survey. 49,60 Out of 40 studies reviewed, only one study reported the longitudinal trajectories of the mental health of North Korean defectors.…”
Section: General Characteristics Of the Included Proms And Studiesmentioning
confidence: 99%
“…Several studies using polysomnography (PSG) to measure sleep architecture, specifically looking at the cyclical pattern of sleep and sleep stage shifts in patients suffering from PTSD, have found abnormal sleep architecture, but the findings are inconsistent (Germain, 2013 ; Kobayashi et al, 2007 ; Lee et al, 2021 ; Maher et al, 2006 ; Mellman et al, 2014 ; Mohsenin & Mohsenin, 2014 ). A meta-analysis on findings from PSG showed decreased total sleep time and sleep efficiency, increased number of awakenings after sleep onset, and decreased amount of slow-wave sleep (Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned inconsistencies in findings regarding sleep quality, sleep architecture, and sleep disorders may be caused by differences between studies concerning adequate controls, demographics, and clinical factors such as gender, age, trauma type, and PTSD severity. No previous studies have compared sleep quality, sleep architecture, and sleep disorders in trauma-affected refugees to HCs (Lee et al, 2021 ). Owing to the above-mentioned potential differences between trauma-affected refugees and other trauma-affected populations, a thorough understanding of these aspects in this specific refugee population may contribute knowledge of importance for enhancing the outcomes of PTSD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although brain structures and functions have been widely studied in other traumatized populations, only a few studies have been performed on alterations of brain structure in traumatized refugees. North Korean (NK) refugees reportedly experience chronic and repetitive trauma after defection from NK, prior to their arrival in South Korea ( 23 25 ). Structural and functional brain changes in NK refugees have been characterized in previous studies ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%